Excesses to permissions and building codes and their impact on the urban environment in Baghdad City - khawla kareem kawther (Iraqi Journal of Architecture and Planning, 2018)
The spreading of the unregulated construction phenomenon in Iraq cities become a serious transgression of the regulations and legislation. The current master plan of Baghdad city no longer responsive to the actual needs of the city, It must be renovation to commensurate with the population growth and city development , so the research problem of this study states that: There are shortcomings in the existing laws and regulations that must keep pace with population, demographic and technology changes, legislation comprehensiveness and not tailored to the requirements of the laws and clauses are applicable, as well as the absence of the city townscape special controls. Based on these facts, the hypothesis of the present study is the importance of applying controls for construction legislation & cities master plan and not violating, by strengthening available means for the municipalities to limit the excesses, there are a number of promotive frames in long-term, and must be a quick and decisive decisions in short term.This study was conducted through a questionnaire survey for the technical staff involved in planning and the research concluded the extent of knowledge of those technical staff about the existence of the legislation and planning laws, their level, its comprehensiveness, its effectiveness, and the effectiveness of the procedures and the extent of its implementation and compliance with. At the end, the study makes recommendations and suggestions to improve the status.Key word: Excesses, codes, urban environment